Immunomodulatory treatment in multiple sclerosis: experience at a Brazilian center with 390 patients - Charles Peter Tilbery; Maria Fernanda Mendes; Bianca Etelvina Santos de Oliveira; Rodrigo Barbosa Thomaz; Giorge Ribeiro Kelian (Arquivos de Neuro-Psiquiatria)
Since 1993 the Federal Drug Administration approved the use of immunomodulatory therapy in multiple sclerosis (MS), modifying the natural course of disease, as demonstrate our experience in treatment of MS patients at the MS Treatment Center (CATEM). OBJECTIVE: To evaluate patient behavior using immunomodulatory therapy for a period of five years treatment. METHOD: We selected 390 patients in CATEM with relapsing-remitting MS (RRMS) and secondary progressive MS (SPMS) with relapses. RESULTS: At initial treatment 292 (61.5%) patients presented RRMS, 98 (20.6%) SPMS with relapses, 27 SPMS (5.6%) and 58 (12.1%) primary progressive MS (PPMS). In RRMS 182 (62.5%) used the interferon beta 1a SC, 15 (5.2%) interferon beta 1a IM, 85 (29%) interferon beta 1b and 10 (3.3%) glatiramer acetate. In SPMS 63 (64.3%) used interferon beta 1a SC, 4 (4.1%) interferon beta 1a IM and 31 (31.4%) interferon beta 1b. We observed that in this period 195 (50%) migrated between drugs, 35 (9%) gave up therapy and 160 (41%) continued the initial therapy. CONCLUSION: Stopping the immunomodulatory therapy emerges as a problem in the second year of treatment and it can be a subset of interferon non responsive or development of neutralizing antibodies.